2016
DOI: 10.1177/0284185116676655
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate and respiration influence on macroscopic blood and CSF flows

Abstract: Background Changes in blood volume in the intracranial arteries and the resulting oscillations of brain parenchyma have been presumed as main initiating factors of cerebrospinal fluid (CSF) pulsations. However, respiration has been recently supposed to influence CSF dynamics via thoracic pressure changes. Purpose To measure blood and CSF cervical flow and quantify the contribution of cardiac and respiratory cycles on the subsequent signal evolution. Material and Methods Sixteen volunteers were enrolled. All pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 18 publications
0
37
0
Order By: Relevance
“…Takizawa et al investigated the relative contributions of the cardiac and respiratory cycles to CSF velocity and CSF displacement, and showed that the contribution of the respiratory cycle to CSF velocity in the aqueduct is smaller compared with the cardiac cycle, but that the resulting total displacement through the aqueduct is larger than the displacements induced by the cardiac cycle. Daouk et al investigated blood and CSF flows using signal intensity changes, and found that arterial blood flow is influenced mostly by the cardiac cycle, while venous blood flow is influenced mostly by the respiratory cycle. CSF appeared to act as a buffer between the arterial and venous blood compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Takizawa et al investigated the relative contributions of the cardiac and respiratory cycles to CSF velocity and CSF displacement, and showed that the contribution of the respiratory cycle to CSF velocity in the aqueduct is smaller compared with the cardiac cycle, but that the resulting total displacement through the aqueduct is larger than the displacements induced by the cardiac cycle. Daouk et al investigated blood and CSF flows using signal intensity changes, and found that arterial blood flow is influenced mostly by the cardiac cycle, while venous blood flow is influenced mostly by the respiratory cycle. CSF appeared to act as a buffer between the arterial and venous blood compartments.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, but not least, recent studies have demonstrated respiration to have a major influence on CSF flow [ 33 , 34 ]. With cardiac gated PC-MRI, which can be considered to represent current state-of-the-art methodology in PC-MRI based measurements of intracranial and intraspinal CSF flow quantification, only cardiac beat induced CSF flow is detected.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those of other studies that have used EPI and showed that respiration and cardiac pulsation both affect CSF movement at the cervical level. 66,67)…”
Section: Analysis Of Csf Motion In the Ventricular Systemmentioning
confidence: 99%